Separate but Related: Dimensions of Healthcare Provider Social Support in Day-Treatment Oncology Units - Tomai, Manuela; Lauriola, Marco (Frontiers in Psychology, 2022)
Social support by healthcare providers has been increasingly investigated during the past decade, but studies have made different choices concerning the measurement of the construct. To evaluate how social support from a healthcare provider impacts the perceived quality of care and patient outcomes, reliable and valid instruments capable of measuring specific aspects of the construct are needed. In study 1, we tested the factor structure and the psychometric properties of a new Healthcare Provider Social Support measure (HPSS) for oncology settings. One-hundred-sixty-two patients (89 females; M age = 58.97, SD age =13.28) from religious and government-operated hospitals completed the HPSS during day treatment. We modeled the HPSS factor structure to represent four related aspects: Emotional, Informational, Appraisal, and Instrumental social support. Study 2 preliminarily assessed the concurrent validity of the HPSS with patient perceptions of the patient-doctor relationship. Sixty-nine patients (40 females; M age = 53.67, SD age = 13.74) completed the HPPS with scales assessing perceived doctor-patient communication and patient trust in the healthcare provider. Study 1, using Exploratory Structural Equation Modeling, showed that a bifactor model had an excellent fit. The analysis supported the use of subscale scores, which were more tenable than a single total score in terms of bifactor model indices. This conclusion was also supported by greater scalability of the subscales in a Mokken Scale Analysis. Oncology patients treated in the religious hospital perceived greater Emotional, Informative, and Instrumental social support from their healthcare provider than those treated in government-operated. Study 2 showed that patient ratings of healthcare provider social support, except Instrumental, were positively correlated with better doctor communication skills and greater trust in the physician. Multiple regression analyses showed that Informational and Emotional support provided a unique contribution to building trust in the physician, controlling for the doctor's communication skills. The study results showed that the four social support ratings were reliable and valid, sharpening the distinction between functional components in the formal healthcare system.